2011
DOI: 10.1111/j.1553-2712.2011.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Case Series of Single‐syringe Ketamine–Propofol (Ketofol) for Emergency Department Procedural Sedation and Analgesia in Adults

Abstract: ACADEMIC EMERGENCY MEDICINE 2011; 18:237–245 © 2011 by the Society for Academic Emergency Medicine Abstract Objectives:  The objective was to evaluate the effectiveness, recovery time, and adverse event profile of intravenous (IV) mixed 1:1 ketamine–propofol (ketofol) for adult procedural sedation and analgesia (PSA) in the emergency department (ED). Methods:  Prospective data were collected on all PSA events over a 4.5‐year period in a trauma‐receiving suburban teaching hospital. PSAs using a 1:1 single‐syrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 46 publications
(67 reference statements)
1
71
1
6
Order By: Relevance
“…In previous studies, the use of a ketofol mixture in a single syringe was suggested as safe for use in an emergency unit and in orthopedic procedures for support of regional anesthesia (17)(18)(19). Willman et al (20) reported that the use of ketofol was safe for painful procedures in an emergency unit.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the use of a ketofol mixture in a single syringe was suggested as safe for use in an emergency unit and in orthopedic procedures for support of regional anesthesia (17)(18)(19). Willman et al (20) reported that the use of ketofol was safe for painful procedures in an emergency unit.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The estimated incidence of recovery agitation in adults receiving ketamine has been reported as between 10% and 20% 34 . Aldonfatto et al 28 have reported that the agitation Propofol has many advantages during sedation such as fast induction, fast recovery and easy regulation of sedation level 7,8 . Its anti-emetic property is an another advantage during sedation.…”
Section: Discussionmentioning
confidence: 99%
“…So a combination with a high ketamine ratio, for example 1:1, may be more beneficial in a short procedural sedation rather than long-term sedation infusions, especially in terms of adverse events. Aldonfatto et al 28 analysed 728 ketofol procedural sedations with a 1:1 ratio and found the combination effective enough in terms of analgesia, recovery times and satisfaction, with few adverse events. Akin et al 29 showed that low-dose ketamine in a cardiac catheterization procedure provided a reduced opioid requirement, with a better haemodynamic profile.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the varying proportion of combination in ketofol (1:1 to 1:10 in mg) for sedation is safe and effective. The combination of the two agents appear to reduce side-effects of each medication used alone, and allows for a rapid recovery time [35,36,[39][40][41][42] . The optimal ratio of ketamine to propofol in ketofol has not been defined yet.…”
Section: Benzodiazepines (Bzd)mentioning
confidence: 99%
“…Incidences of delirium and other side-effects can be minimized by limiting the dose of ketamine or using it in conjunctions with other sedative hypnotic. Commonly used combination medications with ketamine are midazolam, propofol and dexmedetomidine [34][35][36][37] . Ketofol: Combination of ketamine and propofol is called ketofol, is a potentially alternative for procedural sedation, they are mostly combined together in same single syringe and are physically compatible for one hour at 23°C [38] .…”
Section: Benzodiazepines (Bzd)mentioning
confidence: 99%